Characterization of a Potent New-Generation Antimicrobial Peptide of Bacillus - Choyam, Shilja; Jain, Priyanshi M.; Kammara, Rajagopal (Frontiers in Microbiology, 2021)
An antimicrobial peptide [Bacillus antimicrobial peptide (BAMP)] produced by Bacillus paralicheniformis was isolated from the Indian traditional fermented food and characterized. The antimicrobial peptide BAMP showed many unique features such as thermostability (4.0–125°C), pH tolerance (pH 2.0–9.0), and resistance to physiological enzymes (trypsin, chymotrypsin, pepsin, proteinase K, protease, and catalase), and food-grade metal salts do not inhibit the activity. The broad spectrum of BAMP (antimicrobial activity) makes it a suitable candidate for food preservation as well as antimicrobial therapy. BAMP was found to exhibit a bacteriostatic effect on Salmonella typhi and controls the viability of Listeria monocytogenes in chicken meat efficiently. BAMP was found to establish eubiosis, as it is not antagonistic to Lactobacillus. Its non-hemolytic nature makes it suitable for therapy. Various genome prediction tools were adopted and applied to understand their localization, gene arrangement, and type of antimicrobials. Founded on its superior functional attributes, BAMP is a potent new-generation antimicrobial peptide.